Value Relevance Informasi Akuntansi dengan Extended Ohlson Model pada Perbankan BEI Periode 2022-2024 - Anggrelia Afrida; Della Amalia (JUEB : Jurnal Ekonomi dan Bisnis, 2026)
This study aims to examine the Value Relevance of Accounting Information on Banking Stock Prices listed on the Indonesia Stock Exchange from 2022 to 2024. This study uses an associative research approach with population of 27 banks over three years of observation, resulting in 81 research samples using the saturated sampling method. Data analysis was performed using multiple linear regression analysis with the analysis technique of the Statistical Product and Service Solutions (SPSS) program version 25. The results of this study indicate that in the ohlson model, book value per share has a significant effect on stock prices with a significance value of 0,033 while earnings per share does not have a significant effect on stock prices with significance value of 0,246. The extended ohlson model through the addition of financial performance variable shows that net profit margin and current ratio have a significant effect on stock prices with a significance value of 0,000 each. Net profit margin is the most dominant variable in influencing stock prices with a calculated t value of 4,955. These finding indicate that not all accounting information has the same relevance in influencing investor decisions in the capital market. Therefore it is recommended to not only consider the Ohlson model but also to consider the company’s financial performance more comprehensively in making investment decisions.